Radiographic Evaluation of Dental Age in Adults Using Digital Orthopantomograph - Bhavika Sachin Vhatkar; Mandavi Shailesh Waghmare; Naveen Kumar Shetty; Siddharth Acharya; Kapil Sharad Gavand (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Age estimation isimportant for administrative and ethical reasons and because of legal consequences. Dental pulp undergoes regression in size with increasing age due to secondary dentin deposition and can be used as a parameter of age estimation even beyond 25 years of age.Aims and Objectives: The purpose of the present study was to evaluate the feasibility of applying kvaal et al method of age estimation on maxillary second premolar & mandibular first premolar on OPG. Materials and Methods: It is a retrospective study, which involved 100 sample of OPG on KODAK 9000 IMAGING. Measurements were performed on the standardized digital panoramic radiographs based on Kvaal’s method. Different regression formulae were derived and the age was assessed. The assessed age was then correlated to the actual age of the patient using Student’s t-test.Results: In this study, there were no significant difference in estimated & actualage for both males and females.Conclusion: The study was an attempt to use KVAAL et al method of radiographic dental age estimation using OPG with minimal number of teeth.